2006
DOI: 10.1002/jat.1118
|View full text |Cite
|
Sign up to set email alerts
|

Toxicology of fluoroacetate: a review, with possible directions for therapy research

Abstract: Fluoroacetate (FA; CH2FCOOR) is highly toxic towards humans and other mammals through inhibition of the enzyme aconitase in the tricarboxylic acid cycle, caused by 'lethal synthesis' of an isomer of fluorocitrate (FC). FA is found in a range of plant species and their ingestion can cause the death of ruminant animals. Some fluorinated compounds -- used as anticancer agents, narcotic analgesics, pesticides or industrial chemicals -- metabolize to FA as intermediate products. The chemical characteristics of FA a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
76
0
7

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(86 citation statements)
references
References 125 publications
3
76
0
7
Order By: Relevance
“…It is proposed that an increase in the amount of glycogen in the cell cytoplasm is an indicator of diminished usage and accumulation, rather than a sign of increased metabolic activity (Ghadially 1988). The FA interferes in the Krebs cycle and impairs the production of energy by the hepatocytes (Goncharov et al 2006). This impairment could explain the accumulation of glycogen in the liver cells.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is proposed that an increase in the amount of glycogen in the cell cytoplasm is an indicator of diminished usage and accumulation, rather than a sign of increased metabolic activity (Ghadially 1988). The FA interferes in the Krebs cycle and impairs the production of energy by the hepatocytes (Goncharov et al 2006). This impairment could explain the accumulation of glycogen in the liver cells.…”
Section: Resultsmentioning
confidence: 99%
“…However, the available information has not established an unequivocal mechanism by which FA acts on mitochondria. Biochemical studies have implicated FA in the production of the specific aconitase inhibitor fluorocitrate, interruption of the citric acid cycle, and the accumulation of citrate in the mitochondria, an excess of which could provide the basis for an explanation of mitochondrial abnormalities (Bovis et al 1966, Goncharov et al 2006. Swelling of the mitochondria with disruption of the cristae, fluid accumulation in the sarcoplasm and disorganization of the sarcomeres were the main ultrastructural changes observed in all poisoned rabbits.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Gln enters the tricarboxylic acid cycle through glutamate and ␣-ketoglutarate, so we investigated the contribution of the tricarboxylic acid cycle to the induction of MnSOD by utilizing selective inhibitors to several different key enzymes. We first targeted the inhibition of aconitase with 3-fluoroacetate (44,45), which occurs through the intracellular conversion to the aconitase substrate inhibitor, fluorocitrate. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The dog has been shown to be the most sensitive species for this mechanism of action. It is interesting that effects on the heart predominated over central nervous effects in rabbits after the administration of sodium fluoroacetate (Goncharov et al 2006). In rats, heart effects occurred after exposure to 1,3,3,3-tetrafluoropropene and 1,1,1,2,2-pentafluoropropane (Rush et al 2013), while histological heart effects were observed after exposure to 1,3,3,3-tetrafluoropropene and 1,1,1,3,3-pentafluoropropane, but not after 1,1,1,2,2-pentafluoropropane and 2,3,3,3-tetrafluoropropene (Rush et al 2013).…”
Section: M Echanism Of Actionmentioning
confidence: 99%